The Relationship of Reported Neighborhood Conditions with Child Mental Health - Butler, Ashley M. (2012)
OBJECTIVE: While multiple studies have documented the relationship between neighborhood socioeconomic status and child mental health, few have examined the association between neighborhood conditions and mental health disorders. The objective of this study was to determine whether parent-reported neighborhood conditions are associated with common child mental health disorders. METHODS: We analyzed data on children ages 6–17 (N = 64,076) collected through the 2007 National Survey of Children’s Health. Primary outcome variables were a child being reported to have a diagnosis of (a) anxiety and/or depression and (b) attention-deficit hyperactivity disorder (ADHD) and/or disruptive behavior. Main independent variables were parent-reported neighborhood amenities (e.g., recreation center), poor physical characteristics (e.g., dilapidated housing), social support/trust, neighborhood safety, and school safety. Multivariate logistic regression analyses were conducted to examine associations between neighborhood conditions and (a) anxiety/depression and (b) ADHD/disruptive behavior. RESULTS: Children living in a neighborhood with three poor physical characteristics had higher odds of anxiety/depression (AOR 1.58, 95% CI [1.01–2.46]) and ADHD/disruptive behavior (AOR 1.44, 95% CI [1.04–1.99]) compared to children living in a neighborhood with no poor physical characteristics. Children of parents who reported living in a neighborhood with low social support/trust had higher odds of depression/anxiety (AOR 1.71, 95% CI [1.28–2.30]) and ADHD/disruptive behavior (AOR 1.47, 95% CI [1.19–1.81]) than children living in a neighborhood with greater social support/trust. CONCLUSIONS: Parent perception of neighborhood social support/trust and physical characteristics may be important to assess in clinical settings and should be examined in future study of child mental health burden.